The Struggles of Candide for Happiness in Candide, A Novel: An Islamic Perspective - Pepri Cantika, Merli; Pramono, RB. Edi (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
This research discusses Candide's struggle for happiness in Voltaire's Candide from an Islamic perspective. In this study, the researcher discussed two problems, 1) the form of struggle carried out by Candide and 2) the Islamic value of Candide's struggle. The researcher used qualitative methods in this study. The researcher connects Candide's struggle by collecting Qur'anic verses that are following the theme raised. Then, researchers relate to aspects related to the verse through Candide's struggles and actions that are relevant to Islamic values. The form of Candide's struggle can be seen in his personality, such as never give up attitude and positive thinking. Thus, Candide's struggle proved successful as an Islamic struggle because Candide married his lover and lived together, and the value of his struggle for happiness was achieved because of his efforts until the end